POPULATION SIZE OF RED JUNGLEFOWL (GALLUS GALLUS SPADICEUS) IN AGRICULTURE AREAS - Zakaria, Mohamed; Arshad, Muhammad I; Sajap, Ahmad S (Biological Sciences - PJSIR, 2003)
A two-year study was conducted on the population size of Red Junglefowl (Gallus gallus spadiceus) in five agricultural areas in the state of Selangor, Peninsular Malaysia. In the first year (from August 1995 to July 1996) the study was conducted in three habitats viz. rubber plantation, 22-year old oil palm plantation and orchard area at Universitiy Putra, Malaysia. In the second year (from August 1996 to July 1997) two additional habitats viz. 4 and 8 years old oil palm plantation at Sungai, Sedu Estate were selected. Red Junglefowl density was estimated by Distance Sampling Method. Habitat condition was also assessed to determine factors that affected the population size. The densities in 4 years, 8 years and 22 years old oil palm, rubber plantations and orchard were 84.22 km-2, 27.80 km-2, 21.43 km-2, 15.66 km-2 and 6.06 km-2 respectively. The average group size was two birds per group. The largest group comprised of 10 birds was observed in an 8 years old palm oil plantation. The height of the canopy cover was found to have a significant effect on the density of Red Junglefowl. Low canopy cover provides the Red Junglefowl protection against predators and suitable roosting sites.